Knowledge, Attitude and Practice of Medical Ethics Among Dental Professionals in Dental Unit, Chittagong Medical College - Alam, Mohammed Morshed; Sumaiya, Sarah Fatima; Zahur, Tamanna; Yeasmin, Rahela; Barua, Monoj Kumar (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Medical ethics is the disciplined study of morality in medicine and concerns the obligation of Physicians and health care organizations to patients as well as the obligations of patients. Every nation can, however, make certain adjustments and provide unique explanations of medical ethics that are consistent with their own cultures. Like any other profession, dentistry has obligations to both the communities in which it operates and its patients. As it is crucial that dental practitioners comprehend and uphold the code of ethics that has been authorized by Bangladesh's Ministry of Health researchers aimed to assess the awareness, attitude and practice of medical ethics among dental professionals. Materials and methods: This cross-sectional observational study was conducted at Dental Unit in Chittagong Medical College from July 2022 to July 2023, among conveniently selected 80 patients, age ranging from 22 years to 59 years. For data collection a self administered, 30- itemed structured questionnaire encompassing three sections: general information, knowledge, attitude and practice of ethics in dental healthcare professionals was used. Results: Among the respondents 42 (52.5%) were fresh BDS graduates, 18 (22.6%) were lecturers & equivalent, 11 (13.9%) were Assistant Professor & above and the rest 9 (11.3%) were post graduate trainees. Knowledge, attitude and practice were adequate among 86.3%, 95.0% and 91.3% participants respectively. Conclusion: Knowledge, attitude and practice were adequate among the participants. For improving the knowledge and practice education and training could be reiterated for maintaining public trust and ensuring quality patient care. JCMCTA 2024 ; 35 (2) : 170-177